2022
DOI: 10.3390/foods11193021
|View full text |Cite
|
Sign up to set email alerts
|

Ropiness in Bread—A Re-Emerging Spoilage Phenomenon

Abstract: As bread is a very important staple food, its spoilage threatens global food security. Ropy bread spoilage manifests in sticky and stringy degradation of the crumb, slime formation, discoloration, and an odor reminiscent of rotting fruit. Increasing consumer demand for preservative-free products and global warming may increase the occurrence of ropy spoilage. Bacillus amyloliquefaciens, B. subtilis, B. licheniformis, the B. cereus group, B. pumilus, B. sonorensis, Cytobacillus firmus, Niallia circulans, Paenib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 107 publications
1
23
0
Order By: Relevance
“…Sourdough's pH varies depending on the state of fermentation; however, it typically ranges between 3.5 and 5. Harmful microorganisms such as botulism bacteria, E. coli, and spoilage fungi cannot develop in an environment with a pH below 4.6, as this acidity keeps them away [5,57]. We observed that the majority of the strains were able to lower the pH around 4-4.5 (considered a safe pH to avoid spoilage) after 10 h, exhibiting a high acidification ability and underlining the massive production of acids (lactic and acetic acid).…”
Section: Discussionmentioning
confidence: 80%
“…Sourdough's pH varies depending on the state of fermentation; however, it typically ranges between 3.5 and 5. Harmful microorganisms such as botulism bacteria, E. coli, and spoilage fungi cannot develop in an environment with a pH below 4.6, as this acidity keeps them away [5,57]. We observed that the majority of the strains were able to lower the pH around 4-4.5 (considered a safe pH to avoid spoilage) after 10 h, exhibiting a high acidification ability and underlining the massive production of acids (lactic and acetic acid).…”
Section: Discussionmentioning
confidence: 80%
“…Mansuri et al [ 56 ] stated the antibacterial activity of fenugreek oil nanoemulsion against Bacillus subtilis, Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa. The members of Bacillus genus ( B. subtilis, B. cereus, and B. licheniformis ) are the causative organisms for the ropeness phenomenon, which is a bacterial decomposition of the bread making it unsafe and improper for consumption [ 105 ]. Also, Nampuak and Tongkhao [ 106 ] showed that okra mucilage exerted strong inhibitory effects against Bacillus cereus, Staphylococcus aureus and Listeria monocytogenes .…”
Section: Resultsmentioning
confidence: 99%
“…Microbial growth during bread storage produces an unpleasant odour that alters the bread's sensory qualities. They also produce discolouring, slimy rope, and bread crumb degradation by releasing amylase and protease enzymes (Pacher et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%